Reflections on Sustainable Development Planning in the Agricultural Industry - TLESOVA, Aigul; PRIMBETOVA, Saule; KAZAMBAYEVA, Aigul; YESSENGALIYEVA, Saltanat; MUKHAMBETKALIYEVA, Farida (Journal of Environmental Management and Tourism, 2018)
In the past few years, we have experienced a transition from the decades-long period of falling real prices of grains, and food more generally, to a new market environment in which commodity and food prices are higher, more volatile and more highly influenced by petroleum prices. The problems of reaction for price volatility, both in the short- and long-run, are complex and multifaceted. Looking back at the 2007/08 crisis, countries responded through a spectrum of policies, but were largely unprepared, resulting in ad hoc and short-term mechanisms. Countries maintaining food reserves used these to intervene directly in the market to stabilize domestic prices. Many food importing countries reduced import tariffs, while several surplus producing countries limited, or even banned, exports in order to avoid food shortages and further domestic price increases. For whatever actions governments consider taking, it is always important to keep in mind the full set of policy measures, the wider risks and possible responses for the targeted population. The following suggests that choosing appropriate policies requires a deeper understanding of the issues at stake. This paper analyses the various theoretical approaches to the planning of agricultural and food areas of Kazakhstan. The authors consider that the method of forecast scenarios is the most effective one.